Augmented Reality Game-Based Learning: Enriching Students' Experience During Reading Comprehension Activities. (December 2017) - Tobar-Muñoz, Hendrys; Baldiris, Silvia; Fabregat, Ramon
Program for International Student Assessment results indicate that while reading comprehension needs to be promoted, teachers are struggling to find ways to motivate students to do reading comprehension activities and although technology-enhanced learning approaches are entering the classroom, researchers are still experimenting with them to determine their benefits and implications. Among such technology-enhanced learning approaches, we find augmented reality and game-based learning, both of which have proven to be useful in educational settings; nonetheless, few studies have observed them being used jointly. Some open questions to be asked are as follows: Does the use of augmented reality games in the classroom benefit students in terms of performance and motivation? Is the reading activity experience enriched when we use them to promote reading comprehension? In this study, and with the help of teachers, we devised an augmented reality game using a design-based research approach. We then tested it in a real classroom and carried out both quantitative and qualitative observations. Our results show that while results in reading comprehension using the game show no difference to results from the more traditional approaches, children do display greater motivation and interest in the activity and the activity is enriched as it promotes problem solving, exploration, and socialization behavior.